2019
DOI: 10.1016/j.ymben.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional implementation of a linear glycolysis for sugar catabolism in Pseudomonas putida

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 94 publications
(89 reference statements)
1
47
0
Order By: Relevance
“…glycolytic conditions). In a Δ glk mutant of strain KT2440, the bulk of hexoses (80–90%) is oxidized into gluconate, whereas in a Δ gcd mutant, sugars are exclusively phosphorylated to glucose‐6‐ P (Dvořák et al ., ; Sánchez‐Pascuala et al ., , ). Once again, cultures of P. putida KT2440 grown in the aforementioned medium supplemented with CCCP were used to calculate the calibration curve for pH i quantification in all strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…glycolytic conditions). In a Δ glk mutant of strain KT2440, the bulk of hexoses (80–90%) is oxidized into gluconate, whereas in a Δ gcd mutant, sugars are exclusively phosphorylated to glucose‐6‐ P (Dvořák et al ., ; Sánchez‐Pascuala et al ., , ). Once again, cultures of P. putida KT2440 grown in the aforementioned medium supplemented with CCCP were used to calculate the calibration curve for pH i quantification in all strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of glucose in the periplasm yields low‐molecular‐weight organic acids, e.g. gluconate and 2‐ketogluconate (Hirshfield et al ., ; Sánchez‐Pascuala et al ., ). Hence, we set to study how the use of this peripheral pathway influences the pH i in strain KT2440 and its glycolytic mutant derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of genes related to genomic instability (about 4.3 % of the genome) were deleted in KT2440 that resulted in cell-factory strains EM42 and EM383 (a derivative of EM42 deleted for recA gene) with significant increase in ATP and NAD(P)H availability and faster growth of bacteria, reduced sensitivity to oxidative stress and increased expression of heterologous genes [32,123]. Most recently, the glucose catabolism was deeply rewired in P. putida by implanting linear EMP glycolysis route, and the strains with synthetic glycolysis were further engineered for the improved carotenoid synthesis from glucose [124]. The results of this study clearly demonstrated that conserved metabolic features in a platform bacterium can be successfully reshaped for specific biotechnological purposes.…”
Section: P Putida As a Host For Industrial Biocatalysismentioning
confidence: 99%
“…Thereafter, pathway modules have been edited for increasing bioproduction of several molecules, including isoprenoids (48,167,212,(253)(254)(255). Moreover, exclusive exploitation of non-native modules allowed to reduce endogenous control over biochemical routes (256,257). As proof of principle, we assessed if this approach could be applied also to isoprenoid metabolism.…”
Section: Modular Pathway Engineering Allows To Replace Isoprenoid Biomentioning
confidence: 99%